Degradation pathways of Tadalafil: A thermoanalytical study. - Nascimento, Francisco V.B.; Ferreira, Ana P.G.; Gaglieri, Caroline [UNESP]; de Moura, Aniele; Cavalheiro, Éder T.G. (Elsevier, 2025)
Tadalafil (TAD) is one of the most marketed farmaceuticals against erectile dysfunction, due to its large use worldwide it is interesting to understand different aspects regarding this pharmaceutical active ingredient. Thus, in the present study, thermal behavior of TAD was investigated by simultaneous thermogravimetry-differential thermal analysis (TGA-DTA), differential scanning calorimetry (DSC), hot stage microscopy (HSM) and evolved gas analysis using thermogravimetry coupled to vibrational infrared spectroscopy (TGA-FTIR). In addition kinetics of thermal decomposition of the drug was evaluated by non-isothermal kinetic. In atmospheres of N2 and air, TAD, decomposed in different ways in N2 and air atmospheres. DSC curves presented an endothermic event related to the melting of the sample at Tonset = 576 K in the first heating, with no evidence of crystallization under the conditions used here. TGA-FTIR revealed that the thermal decomposition of TAD starts with releasing of 1,3-benzodioxole, carbon monoxide, and propyl isocyanate. The decomposition of the latter results in carbon dioxide and ammonia, which were identified in the gaseous phase and were not directly products from TAD, but by-products from propyl isocyanate. In the HSM, it was possible to observe the complete decomposition of TAD at 573 K, corroborating the results observed in TGA/DTG/DTA and DSC. According to these results, a thermal decomposition mechanism was proposed for TAD. Non-isothermal kinetic studies suggested two consecutive processes, which resulted in just one mass loss in the TGA curve: F1 (Ea = 174, logA = 12.3) and C1 (135 kJ mol−1), 8.3 (1 s−1).
Keywords: Tadalafil; TGA-FTIR; Thermal behavior